2017
DOI: 10.1063/1.4990702
|View full text |Cite
|
Sign up to set email alerts
|

Nudged elastic band calculation of the binding potential for liquids at interfaces

Abstract: The wetting behavior of a liquid on solid substrates is governed by the nature of the effective interaction between the liquid-gas and the solid-liquid interfaces, which is described by the binding or wetting potential g(h) which is an excess free energy per unit area that depends on the liquid film height h. Given a microscopic theory for the liquid, to determine g(h) one must calculate the free energy for liquid films of any given value of h; i.e. one needs to create and analyse out-of-equilibrium states, si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…However, alternatively to such combinations of different asymptotic expressions it has recently been shown that one may directly extract wetting energies (and interfacial tensions) from various microscopic models, namely, Molecular Dynamics (MD) simulations [120], lattice Density Functional Theory (DFT) [18,52] and continuous DFT [53] for Lennard-Jones fluids and other simple liquids. Refs.…”
Section: Obtaining Wetting Potentials From Microscopic Modelsmentioning
confidence: 99%
“…However, alternatively to such combinations of different asymptotic expressions it has recently been shown that one may directly extract wetting energies (and interfacial tensions) from various microscopic models, namely, Molecular Dynamics (MD) simulations [120], lattice Density Functional Theory (DFT) [18,52] and continuous DFT [53] for Lennard-Jones fluids and other simple liquids. Refs.…”
Section: Obtaining Wetting Potentials From Microscopic Modelsmentioning
confidence: 99%
“…Here, we use the approach of Refs. [23,24] (see also [25,26]) that uses classical density functional theory (DFT) [27][28][29] to calculate the binding potential g(h), from which one obtains Π(h) = −∂g(h)/∂h, and also the interfacial tensions. Thin-film equations together with binding potentials from DFT have been used previously to elucidated the influence of the fluid microscopic structure on droplet spreading [30].…”
Section: Introductionmentioning
confidence: 99%
“…Note that continuation techniques may also be applied to deterministic lattice models or stochastic models [31,34]. This implies that it should in the future also be possible to apply the proposed method to analyse the phase behaviour for lattice DFT and Monte Carlo models as studied, e.g., in [4,7].…”
Section: Discussionmentioning
confidence: 99%